Analysis of factors influencing the production and marketing of salted anchovies in Barru District, Sumpang Binangae Village, Barru Regency - Bado, Basri; Hasriyuni; Kamaruddin, Citra Ayni (Economics and Business Journal (ECBIS), 2024)
This research aims to determine what factors influence the production and marketing of salted anchovies in Barru District, Sumpang Binangae Village, Barru Regency. The data used in this research are primary and secondary data. The analytical method used in this research is multiple linear regression analysis. The results of the research show that the factors that influence the production of salted anchovies in the variables of labor (X1) and capital (X2) simultaneously have a significant effect on the amount of salted anchovy production in Barru District, Sumpang Binangae Village, Barru Regency. The marketing channels for salted anchovies in Barru District, Sumpang Binangae Village, Barru Regency consist of 3 (three) marketing channel patterns, namely: salted anchovy processors-consumers; (2) salted anchovy processor-trader collector-consumer; (3) salted anchovy processors- collecting traders- retailers- consumers. The lowest marketing margin value is marketing channel I, namely IDR. 640/Kg while the highest marketing margin value in channel III is Rp. 8,640/Kg.